A perspective on critical thinking, debate, higher education in Bangladesh - Fatima Tuz Zahra (BRAC University, 2013)
The aim of higher education is to pursue learning for its own sake and to develop specialist skills. However due to market pressure higher education institutions in Bangladesh and across the world have had to focus on practical skills rather than inculcating a desire for knowledge. There is more emphasis to secure jobs than making students curious about knowledge and learning. Alongside this pragmatic approach there is a lot of importance given to critical thinking skills in the higher education curriculum. However, despite its centrality in the curricula most academic institutions follow a simplistic form of teaching critical thinking skills, which focus on the skill of breaking down arguments into its parts and ignores modes of thought which might facilitate solutions. This paper looks at the elements of critical thinking as it applies to the educational practices in higher education institutions in Bangladesh, and how the classical art of rhetoric, manifested in the extracurricular activity of debate, functions towards rote reproduction rather than initiating the process to think critically.